Effects of temperature and time on free formaldehyde emission of composite product / Nur Mahira Haji Jusoh - Haji Jusoh, Nur Mahira (Faculty of Applied Sciences, 2017)
This study investigated effects of temperature and time on free formaldehyde emission of composite product from MDF E2 grade measured by the Japanese Industry Standard (JIS A 5908) with desiccator method and build the regression equation based on temperature and time by using Response Surface Methodology (RSM). The result shows that temperature and time have significant effect on free formaldehyde emission. The regression produced the equation of HCHO = 0.89715 - 0.058605 (T) - 0.027454 (t) + 0.001080833 (T)2 + 0.000502315 (t)2 + 0.000583333 (T)(t).